ANALYSIS OF EMPLOYEE SWITCHING INTENTIONS IN MULTI-LEVEL MARKETING (MLM) COMPANIES: A QUALITATIVE STUDY RELATING TO ETHICAL LEADERSHIP - Siti Alfia Ayu Rohmayanti; Praptini Yulianti (Media Bina Ilmiah, 2023)
This study discusses the factors that can reduce employee turnover intentionthrough Ethical Leadership. The focus of this research is to find out the factors that cause partners to have the turnover intention to another company or not to cooperate with the company they have participated in. This research was conducted using a qualitative method, namely a review of the level of understanding of the Multi Level Marketing business people. In this study using observations in the area of Surabaya and Sidoarjo. This is done with several considerations, namely: First, the research location is close to the reach of the researcher. Second, several leaders and business headquarters are located in Surabaya and Sidoarjo. The sample was taken using purposive sampling because the researcher needed informants who had sufficient experience and knowledge in the business environment. From the results of the interview, it is known that the role of the upline as a leader in the business has a major influence on the development of the network. In addition, it turns out that motivational factors also have an influence on downline decisions on turnover intention. In addition, what is needed is not only a supportive leader in providing training but also an ethical attitude.